The genome and diet of a 35, 000‐year‐old Canis lupus specimen from the Paleolithic painted cave, Chauvet‐Pont d'Arc, France. Issue 8 (23rd August 2022) - Elalouf, Jean‐Marc; Palacio, Pauline; Bon, Céline; Berthonaud, Véronique; Maksud, Frédéric; Stafford, Thomas W.; Hitte, Christophe
Abstract: The Chauvet‐Pont‐d'Arc Cave (Ardèche, France) contains some of the oldest Paleolithic paintings recorded to date, as well as thousands of bones of the extinct cave bear, and some remains and footprints of other animals. As part of the interdisciplinary research project devoted to this reference cave site, we analyzed a coprolite collected within the deep cave. AMS radiocarbon dating of bone fragments from the coprolite yielded an age of 30, 450 ± 550 RC yr. BP (AAR‐19656; 36, 150–34, 000 cal BP), similar to ages assigned to Paleolithic artwork and cave bear remains from the same cave sector. Using high‐throughput shotgun DNA sequencing, we demonstrated a high abundance of canid DNA and lesser amounts of DNA from the extinct cave bear. We interpret the sample as feces from a canid that had consumed cave bear tissue. The high amount of canid DNA allowed us to reconstruct a complete canid mitochondrial genome sequence (average coverage: 83×) belonging to a deeply divergent clade of extinct mitochondrial wolf lineages that are most closely related to coeval ( 35 ka) Belgian wolves. Analysis of the nuclear genome yielded a similar coverage for the X chromosome (2.4×) and the autosomes (range: 2.3–3.2×), indicating that the Chauvet canid was a female. Comparing the relationship of the nuclear genome of this specimen with that of a variety of canids, we found it more closely related to gray wolves' genomes than to other wild canid or dog genomes, especially wolf genomes from Europe and the Middle East. We conclude that the coprolite is feces from an animal within an extinct wolf lineage. The consumption of cave bear by this wolf likely explains its intrusion into the dark cave sectors and sheds new light on the paleoecology of a major cave site. Abstract : We analyzed a coprolite (fossil feces) from the Paleolithic painted cave of Chauvet‐Pont d'Arc (Ardèche, France). AMS radiocarbon dated yielded an age of 30, 450 ± 550 radiocarbon yr. BP (36, 150–34, 000 cal BP), similar to ages assigned to Paleolithic artwork from the same cave sector. Using high‐throughput ancient DNA sequencing, we demonstrate that the coprolite corresponds to feces produced by a female gray wolf that had consumed cave bear tissue; the Chauvet wolf specimen is more related to Eurasian gray wolves than to domestic dogs, especially ancient Western Eurasian wolves that delineate an extinct lineage.